FEATURES OF VOLUNTEER IT-PROJECTS IN THE SOCIAL ECONOMY - Ноздріна , Лариса; Фалат, Максим (Socio-economic relations in the digital society, 2020)
The purpose of this article is to describe the theoretical and methodological approaches to the management of volunteer projects. The article describes the principles of volunteering in the social economy. The state of development of social economy and volunteer activity in the world and in Ukraine is analyzed. It is noted that volunteering has significant economic potential and is a means of uniting and developing civil society. Possibilities of realization of volunteer activity under the project approach are considered. The classification of volunteer projects with the selected classification feature of IT support is offered. Features of volunteer IT-projects are described. The principles of implementation of the volunteer project of creation of the platform of support of volunteer activity «HSRG-DIS» by means of a flexible methodology of management of projects and software for its realization are developed. The article proposes an approach to determining the effectiveness of a volunteer IT-project. During the development of HSRG-DIS’s own project, the following features of volunteer IT-projects were identified: 1) the possibility of scaling the project; 2) financing of the project by the state and individuals; 3) rapid storage and dissemination of project data; 4) the possibility of timely updating and support of the project; 5) checking the priorities and attitudes of users; 6) use of modern IT and technical means of project development and data analytics. It is substantiated that one of the ways to improve the development of volunteer IT-projects is a combination of iterative and incremental approaches used in modern models of planning IT-projects. In particular, these approaches suggest that: the requirements for the system and its architecture are processed more than once, but gradually refined from iteration to iteration (iterative approach); the result of each iteration is a version of the software product that implements part of the functionality of the future software product and can be put into test or experimental operation, as well as evaluated by the customer and future users (incremental approach).
Keywords: social economy; volunteering; classification of volunteer projects; volunteer IT-project; HSRG-DIS; IT-platform; effectiveness of volunteer IT-project